Sex differences in sarcopenia and frailty among community‐dwelling Korean older adults with diabetes: The Korean Frailty and Aging Cohort Study. Issue 2 (8th August 2020) - Kang, Sunyoung; Oh, Tae Jung; Cho, Be Long; Park, Yong Soon; Roh, Eun; Kim, Hyeon Ju; Lee, Sam‐Gyu; Kim, Bong Jo; Kim, Miji; Won, Chang Won; Jang, Hak Chul
Abstract: Aims/Introduction: We aimed to examine the prevalence of sarcopenia and frailty in Korean older adults with diabetes compared with individuals without diabetes. Materials and Methods: We analyzed the data of 2, 403 participants aged 70–84 years enrolled in the Korean Frailty and Aging Cohort Study. Sarcopenia was defined using the Asian Working Group for Sarcopenia and the Foundation for the National Institutes of Health. Frailty was assessed by the Cardiovascular Health Study frailty phenotype criteria. Results: The mean age of the participants was 76.0 ± 3.9 years, and 47.2% were men. The prevalence of diabetes was 30.2% in men and 25.8% in women. Adults with diabetes showed a lower muscle mass index (appendicular skeletal muscle mass/body mass index) and handgrip strength in both sexes, but only the women showed decreased physical performance. Women with diabetes presented a higher prevalence of sarcopenia diagnosed by the Foundation for the National Institutes of Health criteria, and frailty compared with participants without diabetes (sarcopenia 14.7% vs 8.5%, P  = 0.001; frailty 9.5% vs 4.9%, P  = 0.003). Men in the high and middle tertiles for homeostatic model assessment of insulin resistance presented a significantly higher prevalence of sarcopenia, compared with men in the low tertile homeostatic model assessment of insulin resistance (high tertile 16.6%, middle tertile 13.3%, low tertile 8.6%). Conclusions: In older adults with diabetes, muscle mass index and muscle strength were lower than in those without diabetes. However, the prevalence of sarcopenia and frailty was higher and physical performance was lower only in women with diabetes. Abstract : We aimed to examine the prevalence of sarcopenia and frailty in Korean older adults with diabetes compared with adults without diabetes using a nationwide cohort study. The muscle mass index and muscle strength in older adults with diabetes were lower than in those without diabetes. However, the prevalence of sarcopenia and frailty was higher, and physical performance was lower only in women with diabetes.